Both the changes of six amino acids and the C-terminal truncation caused by a one-base insertion in the defective env gene of Friend spleen focus-forming virus significantly affect the pathogenic activity of the encoded leukemogenic membrane glycoprotein (gp55). - Watanabe, N (1995)
Friend spleen focus-forming virus (F-SFFV) causes acute erythroleukemia in mice and encodes in its defective env gene an Env-like membrane glycoprotein (gp55). The F-SFFV env gene has three characteristic structures compared with that of ecotropic murine leukemia viruses (MuLVs): substitution by the polytropic MuLV env sequence, a 585-bp deletion, and a 1-bp insertion. All of these characteristic structures are essential for the leukemogenic potential of gp55 of polycythemia-inducing isolates of F-SFFV (F-SFFVp). The 1-bp insertion causes changes of six amino acids and truncation by 34 amino acids at the C terminus. In this study, we constructed 12 mutant F-SFFV genomes starting from the wild-type F-SFFVp and examined the effect of the C-terminal truncation and the six altered amino acids on the pathogenic activity of gp55. The results indicated that at least 18 to 24 amino acids must be deleted from the C terminus for the env product to be pathogenically active. We also found that the six altered amino acids contributed significantly to the pathogenic activity of gp55. Analyses of the cellular processing of these mutant gp55s supported a correlation between the pathogenic activity of gp55 and its efficiency in overall cellular processing.